Penerapan AI untuk Deteksi Penyakit Tanaman dan Pestisida Nabati di Desa Kutamandiri - Iin, Iin; Suherman, Jajang; Trianto, Topan (Jurnal Pengabdian Tri Bhakti, 2025)
This community engagement program aims to utilize Artificial Intelligence technology, specifically ChatGPT, to assist farmers in Kutamandiri Village in identifying plant diseases and formulating botanical pesticides from local plants. Using smartphones and internet access, farmers were guided to describe symptoms found on rice, corn, and sweet potatoes to ChatGPT, which then provided diagnostic suggestions and treatment recommendations. Additionally, ChatGPT was used to explore the chemical properties of local wild plants such as wild turmeric, fingerroot, and galangal, and to obtain practical instructions for making organic pesticides. The results showed that farmers' interactions with AI improved their understanding, independence, and technological adoption in daily agricultural practices. ChatGPT proved to be an effective digital assistant that is responsive and accessible to rural communities. This program demonstrates that AI can serve as a powerful empowerment tool to bridge the information and resource gap in the agricultural sector.